Optimisation of enzyme-aided peeling of musk lime (Citrus mitis B.) and development of its candied peel - Adnan, Hazniza (2003)
Studies on the optimisation of enzyme peeling of citrus fruits were carried out on musk lime (Citrus mitis B.). The time taken to peel musk lime by enzyme (Peelzym II) was minimised with increasing enzyme concentration and application of vacuum pressure. The optimum enzyme concentration and optimum vacuum pressure for peeling musk lime peel was 1.0% (v/w) and 700 mm Hg, respectively. The effect of vacuum pressure in physico-chemical changes of peeled fruits of musk lime (Citrus mitis B.) during enzymatic peeling was studied. The pH, total soluble solids, citric acid, ascorbic acid, moisture, total pectin, tannin and sugar contents in the puree of peeled musk lime were not significantly affected by the vacuum pressure, except, total pectin content and 'b' value of puree colour at very high vacuum pressure (700 mm Hg). The naringin content has also been analysed in the puree, seeds and peel (discarded) of peeled musk lime. The lime. The naringin content in the puree and seeds of peeled musk lime were not significantly affected by the vacuum pressure, however, naringin content in the peel was significantly affected at very high vacuum pressure. The development of candied musk lime peel was carried out using Response Surface Methodology (RSM) and ECHIP® software. In this study, the RSM method was found to be effective in making a new product when the developed product (candied musk lime peel) had matched the sensory profile of a target product (commercial candied peel). This method was then confirmed by a verification process between the experimental value from the developed product (candied musk lime peel) with the target value obtained from the overlapping contour maps of ingredients in the making of optimum candied musk lime peel. Results from sensory evaluation also showed that most of the panelists liked the taste of the product compared to other sensory attributes tested. In comparison, the developed candied musk lime peel has a similar profile in terms of appearance, odour and taste of sourness and bitterness to that of commercial candied peel. Therefore, the candied musk lime peel developed in this study has the potential to be commercialised.